Study into formation of cobalt-containing peo-coatings on AK12M2MgN from a pyrophosphate electrolyte - Karakurkchi, A.; Sakhnenko, M.; Ved, M.; Horokhivskyi, A.; Galak, A. (Технологический центр, 2017)
We studied the process of formation of cobalt-containing oxide coatings using plasma-electrolytic oxidizing of the aluminum alloy AK12M2MgN in pyrophosphate electrolytes. It was established that the use of given type solutions contributes the homogenization of silumin surface and creates preconditions for the dopants incorporation to the growing oxide coating. It is shown that PEO parameters depend on the concentration ratio of cobalt sulfate and potassium pyrophosphate in a working solution. Based on the results of experimental study, we demonstrated the ways to control the structure and surface morphology of cobalt-containing PEO coatings through the variation in the concentrations of electrolyte components. The composition of a pyrophosphate electrolyte for the formation of oxide PEO-coatings with a high cobalt content and developed surface morphology is substantiated. It is noted that the obtained oxide coatings could be used in catalytic reactions in order to decompose natural and technogenic toxicants.

Досліджено формування кобальтовмісних оксидних покривів методом плазмово-електролітичного оксидування силуміну АК12М2МгН у пірофосфатних електролітах. Показано, що варіювання концентрації кобальту сульфату в розчині впливає на робочі параметри ПЕО. Встановлено, що склад та морфологія сформованих оксидних шарів залежать від співвідношення компонентів електроліту. Це дозволяє керувати процесом інкорпорації допанта в матрицю оксиду алюмінія. Обгрунтовано склад пірофосфатного електроліту для одержання оксидних покривів, збагачених каталітичним компонентом.
Keywords: oxide coating; silumin; plasma-electrolytic oxidizing; pyrophosphate electrolyte; surface morphology; покрив оксидний; силумін; оксидування плазмово-електролітичне; електроліт пірофосфатний; морфологія поверхні